2018
DOI: 10.3892/mmr.2018.9449
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of α‑2‑macroglobulin on human bone marrow mesenchymal stem cells in radiation injury

Abstract: Osteoradionecrosis of the jaws (ORNJ) is a complication of oral and maxillofacial malignancy that arises following radiotherapy; progressive jaw necrosis severely decreases the quality of life of patients. Human bone marrow mesenchymal stem cells (hBMMSCs) are a cell type with self-renewal and pluripotent differentiation potential in the bone marrow stroma. These cells are associated with bone tissue regeneration and are one of the primary cell types affected by bone tissue radiation injury. α-2-macroglobulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 31 publications
(29 reference statements)
0
12
0
Order By: Relevance
“…Our previous study found that there was a positive correlation between serum α2M levels and the dose of radiotherapy in patients with nasopharyngeal carcinoma. In addition, we also found that α2M protected the osteogenic potential of bone marrow mesenchymal stem cells after radiation . Therefore, we hypothesized that α2M may be able to protect against jaw ORN.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Our previous study found that there was a positive correlation between serum α2M levels and the dose of radiotherapy in patients with nasopharyngeal carcinoma. In addition, we also found that α2M protected the osteogenic potential of bone marrow mesenchymal stem cells after radiation . Therefore, we hypothesized that α2M may be able to protect against jaw ORN.…”
Section: Introductionmentioning
confidence: 85%
“…In addition, we also found that α2M protected the osteogenic potential of bone marrow mesenchymal stem cells after radiation. 11 Therefore, we hypothesized that α2M may be able to protect against jaw ORN.…”
mentioning
confidence: 99%
“…In addition, a previous study reported that the rat acute-phase α2M protein serves a central role in amifostine-mediated radioprotection, increasing the protective effect by 45-fold (19). As demonstrated in a study from our laboratory, α2M maintains the osteogenic potential of human bone marrow mesenchymal stem cells (hBMMSCs) following IR (20). In particular, hBMMSCs are among the main cells damaged during bone tissue radiation (21,22).…”
Section: Introductionmentioning
confidence: 87%
“…Improved 3D-printed mandible fixtures and a lead sheet were used to precisely deliver radiation to the mandible and protect the surrounding tissues by shielding them from IR. The dosage was based on an extensive review of the literature (25,26) and previous work from our laboratory (20). All rats were fed a liquid diet during the first week after IR.…”
Section: Establishment Of the Orn Animal Model A Total Of 72mentioning
confidence: 99%
See 1 more Smart Citation